Assessment of structural and hemodynamic performance of vascular stents modelled as periodic lattices. (July 2018) - Prithipaul, Purnendu K.M.; Kokkolaras, Michael; Pasini, Damiano
Highlights: Systematic use of a unit cell approach, commonly used for lattices, to evaluate stent performance. Stent mechanics metrics given for foreshortening, elastic recoil and radial stiffness. Hemodynamic performance defined from statistical moments of wall shear stress distribution. Combined assessment of mechanics and hemodynamic performance for five stent geometries. Abstract: This work considers vascular stents with tubular geometry assumed to follow a periodic arrangement of repeating unit cells. Structural and hemodynamic metrics are presented to assess alternative stent geometries, each defined by the topology of the unit cell. Structural metrics include foreshortening, elastic recoil and radial stiffness, whereas hemodynamic performance is described by a wall shear stress index quantifying the impact of in-stent restenosis. A representative volume element (RVE) modelling approach is used, and results are compared to those obtained from full simulations of entire stents. We demonstrate that the RVE approach can be used to quantify the impact of the topology of the repeating unit on the structural and hemodynamic properties of a stent, and thus support clinicians in making proper choices among alternative stent geometries.